Sleep deprivation during a specific 3-hour time window post-training impairs hippocampal synaptic plasticity and memory - Prince, Toni-Moi (2013)
Sleep deprivation disrupts hippocampal function and plasticity. In particular, long-term memory consolidation is impaired by sleep deprivation, suggesting that a specific critical period exists following learning during which sleep is necessary. To elucidate the impact of sleep deprivation on long-term memory consolidation and synaptic plasticity, long-term memory was assessed when mice were sleep deprived following training in the hippocampus-dependent object place recognition task. We found that 3 hours of sleep deprivation significantly impaired memory when deprivation began 1 hour after training. In contrast, 3 hours of deprivation beginning immediately post-training did not impair spatial memory. Furthermore, a 3-hour sleep deprivation beginning 1 hour after training impaired hippocampal long-term potentiation (LTP), whereas sleep deprivation immediately after training did not affect LTP. Together, our findings define a specific 3-hour critical period, extending from 1 to 4 hours after training, during which sleep deprivation impairs hippocampal function.